RESPONS TERHADAP KONSEPSI ALLAH DALAM TEOLOGI PROSES - Hermawan Hermawan (Sekolah Tinggi Alkitab Tiranus, 2019)
Process theology has influenced the worldview of Christian theology. It has emphasis on the doctrine of God. Process theology is consistently applied based on dipolar nature, namely the changing and unchanging nature. These two natures have affected the view of God. Process theology is also included as natural theology, which is seeking for theodicy purpose. In this article, there are two types of response toward process theology, appreciation and counter position. The responses will be elaborated based on theological concept and biblical studies approaches.